How to apply TMT for generic substitution in Ramathibodi CPOE - Thawitangkkul, Sarayut; Pattanaprateep, Oraluck (Journal of the Thai Medical Informatics Association, 2022)
Generic substitute is a process of changing medicine which has the same generic name, dosage form, and strength of different trade name from another pharmaceutical company. It happens when the pharmacy department has to change vendor or manufacturer or when it is between the changing stock periods. The consequence is it delayed administration time of patient while waiting physician to prescribe the new prescription. This study aims to analyze the in-patient prescribing process and apply Thai Medicinal Terminology (TMT) Trade Product Unit (TPU) and Generic Product Unit (GPU) of 91 generic medicines in Computerized Physician Ordering Entry (CPOE). Total 36,488 in-patient prescriptions which has been prescribed any of 91 interesting items between 1 January 2018 and 31 December 2018 were included. Average time from physician prescribing to ward was at 40.60 minutes (SD = 49.87) and median time at 20.00 minutes. The time would be less at least 40 minutes if this new system could be implemented.